Definition of 'abandoned housing project' in Peninsular Malaysia: Should there be a legal definition? - Md Dahlan, Nuarrual Hilal (2007)
Although there are administrative definitions on 'abandoned housing project' in Peninsular Malaysia issued by the Division of Supervision and Enforcement, Malaysian Ministry of Housing and Local Government (MOH), yet the definitions given, seems, have not been satisfactory.Further there is no statutory nor legal definition over the same resulting in certain confusion and uncertainty on the true meaning of 'abandoned housing project' occurring in Peninsular Malaysia.This paper will discuss the definitions and criticize their perimeters and possible meanings towards achieving the better definition either legal, statutory and administrative definition of 'abandoned housing project' in Peninsular Malaysia.